The problem of selecting digital development priorities for the region and ways of its solution - S. S. Kabanov (Вестник университета)
The article discusses the problems of choosing digital development paths for the region, using the Nizhny Novgorod region as an example. Based on the hierarchy analysis method, regional policy priorities for deepening digitalisation processes have been determined. Alternative directions for the region’s digital development have been proposed in terms of priorities for improving information and communication infrastructure, enhancing human resources capacity, creating new digital technologies and investments in digitalisation. The necessity of integration of federal and municipal information systems and development of advanced production technologies related to information and communication technologies necessary to ensure the competitiveness and economic security of enterprises in the Nizhny Novgorod region has been substantiated.